Pseudo Problems in Christian Theology - Dick Osita Eugenio (Sekolah Tinggi Theologia Nazarene Indonesia, 2023)
As a scientific theologian, Thomas F. Torrance advocated for an objective approach to theologizing. He was weary of approaching the contents of divine revelation out of a center in philosophy, culture, or the self. For him, an imposition to theology from without creates problems to theological content. This article focuses on his analysis of the Greek understanding of space that became the underlying—and unspoken—presupposition of early heretics that led them to advocate Christological profanity. Using qualitative content analysis as research design, the article scoured through Torrance’s own writings and secondary literature to present Torrance’s critique of philosophical theology and his own theological alternative. Greater emphasis, however, was given to primary sources so that Torrance’s own position is faithfully presented. The study is sympathetic to Torrance’s proposal that Christian theology may avoid doctrinal and theological problems if theologians interpret divine realities kata physin. Using the concept of space as an illustration, both in the past and the present, if both biblical and theological scholarships operate within cultural-philosophical categories and not from a center in the Gospel datum taken at face value, problems that are not supposed to be there surface. Theologizing becomes circularly self-collapsing once prevailing popular and cultural worldviews are uncritically assimilated and accepted.